A-4=B
2+C=B
A+B+C=13
A=b+4
C=B-2
Plug in to equation 3
(B+4)+B+(B-2)=13
Rearrange
B=11/3
A=(11/3)+4= 23/3
C=(11/4)-2= 3/4
Answer:
approximately 3.16 repeated
Step-by-step explanation:
Answer:
<u>Given expression:</u>
<u>The first root is valid when:</u>
- 2x + 2 ≥ 0 ⇒ 2x ≥ - 2 ⇒ x ≥ - 1
<u>The second root is valid when:</u>
- 6 - 4x ≥ 0 ⇒ 4x ≤ 6 ⇒ x ≤ 1.5
<u>So the variable x can get values within interval:</u>
- -1 ≤ x ≤ 1.5 or
- x = [-1, 1.5]
Answer: 72 HOPE THIS HELPS!
Answer:
Not a native English speaker, but ig this is what u want:
Step-by-step explanation:
6(3x+4)=15x+24